2006
DOI: 10.2215/cjn.01701105
|View full text |Cite
|
Sign up to set email alerts
|

Safety and Adverse Events Profiles of Intravenous Gammaglobulin Products Used for Immunomodulation

Abstract: Intravenous Ig (IVIg) products are used in various medical conditions. Differences in excipients account for most adverse events (AE). Reports of complications including acute myocardial infarction (AMI) and acute renal failure (ARF) have emerged. Herein is described one institution's experience with IVIg-related complications. This study is a retrospective analysis of infusion-related AE that are associated with various IVIg products. Infusion-related AE were monitored during and after the administration of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
45
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 74 publications
(45 citation statements)
references
References 31 publications
(31 reference statements)
0
45
0
Order By: Relevance
“…Our group has extensive experience with monitoring the efficacy and safety of IVIG products used in desensitization and for the treatment of AMR (8,9,17). However, our recent experience with newer, isosmolar, liquid products has shown an unexpected risk of IH that was not seen with older products and seems to be related to an increased titer of anti-A/B antibodies in liquid IVIG products.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Our group has extensive experience with monitoring the efficacy and safety of IVIG products used in desensitization and for the treatment of AMR (8,9,17). However, our recent experience with newer, isosmolar, liquid products has shown an unexpected risk of IH that was not seen with older products and seems to be related to an increased titer of anti-A/B antibodies in liquid IVIG products.…”
Section: Discussionmentioning
confidence: 99%
“…However, this is likely not feasible at all medical centers because of pharmacy purchasing practices. In addition, side effects such as acute renal failure or thrombosis can occur with the higher osmolar products, thereby limiting their use in some situations (8). There has been mixed success preventing hemolytic reactions by removing the antibodies from the IVIG product in vitro (20,21).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, a retrospective study at Cedars-Sinai Medical Center found that all five of their patients that suffered IVIg associated myocardial infarction had received a preparation with a particularly high osmolality (1,179 mOsm/kg). [39] Our institution uses Gammagard 10% (Baxter industries), the osmolality of which is 240-300 mOsm/kg, which is similar to physiologic osmolality. The reason why our patient would suffer from apparent hyperviscosity and acute myocardial infarction after receiving this infusion is unclear; however, the temporal relationship between administration of IVIg and development of symptoms makes this a compelling explanation.…”
Section: Published By Sciedu Pressmentioning
confidence: 99%